2014
DOI: 10.4143/crt.2014.017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Primary Spinal Cord, Spinal Meninges, and Cauda Equina Tumors in Korea, 2006-2010

Abstract: PurposePrimary spinal cord and appendage tumors (PSCAT) originating from the spinal cord, spinal meninges, and cauda equina are uncommon. Worldwide, population-based cancer registry data are mostly based on malignant tumors only, which means few data are available on PSCATs, including non-malignant tumors. Therefore, the objective of this study was to provide information regarding the incidence of both non-malignant and malignant PSCATs in Korea on a national level.Materials and MethodsIncidence of PSCATs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
7
8
0
2
Order By: Relevance
“…On the other hand, incidence of primary malignant spine tumor was lower in women than that in men (Table 2). This tendency was similar to previous a recent Korean study7) and previous studies of the United States3,15).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, incidence of primary malignant spine tumor was lower in women than that in men (Table 2). This tendency was similar to previous a recent Korean study7) and previous studies of the United States3,15).…”
Section: Discussionsupporting
confidence: 93%
“…The second most common tumor type was a neoplasm of the vertebral column among the primary malignant tumors and neoplasm of the spinal meninges among the primary nonmalignant spine tumors. This tendency is in good agreement with a histology based nationwide Korean study7). As we described in our previous study, this tendency is in line with previous studies which found that spinal cord tumors were the most common, followed by spinal meninges tumors 3,15).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…3 extramedulares ou intradurais intramedulares. O schwannoma é um tumor de bainha nervosa, sendo, portanto, intradural extramedular, embora alguns possam crescer a ponto de terem componente extradural ou mesmo serem completamente extradurais, 1,4 havendo inclusive relato de casos em que o schwannoma não se liga ao tecido nervoso.…”
Section: Discussionunclassified